El juego motor en el desarrollo de la lateralidad de los niños de inicial II de 4 a 5 años, paralelo “A” de la unidad educativa Verbo Divino, del Cantón Guaranda, provincia Bolívar, año 2023. - Guachi Pilco, Tannia Michelle (2024)
This research project was carried out on the topic: Motor game in the development of laterality in children of Initial II from 4 to 5 years old, parallel “A” of the Educational Unit “Verbo Divino”. For its effect, bibliographic sources were used, the focus of our research is mixed since we worked with 30 children and a teacher, the type of research is descriptive and explanatory, inductive and deductive methods, analysis- synthesis, research- action were improved, and for the collection of information the observation sheet and survey were applied; through the instrument such as the questionnaire, which they attribute to us to determine if the motor game affects the development of laterality. It is known that in the “Verbo Divino” Educational Unit there is a problem of ignorance about the application of the game to develop laterality, where it is determined that boys and girls are unaware of their lateral dominance, which brings with it consequences, since they do not go to have children adequate skills that are essential in everyday life. In scientific theory we make known the importance of the development of laterality in children since it helps them for their spatial orientation, language, spatial notion and later for literacy, thus improving their potential. The teacher has not developed lateral dominance in children, therefore her laterality is deficient, for which the application of motor play is proposed to motivate teaching and learning in children, therefore, the realization of an activity guide that will serve as a tool for the teacher